2009
DOI: 10.1088/0004-637x/704/1/870
|View full text |Cite
|
Sign up to set email alerts
|

Swaying Threads of a Solar Filament

Abstract: From recent high resolution observations obtained with the Swedish 1-m Solar Telescope in La Palma, we detect swaying motions of individual filament threads in the plane of the sky. The oscillatory character of these motions are comparable with oscillatory Doppler signals obtained from corresponding filament threads. Simultaneous recordings of motions in the line-of-sight and in the plane of the sky give information about the orientation of the oscillatory plane. These oscillations are interpreted in the conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
186
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(201 citation statements)
references
References 32 publications
15
186
0
Order By: Relevance
“…Recent observations of Alfvénic transverse waves in spicules have been reported by, e.g, De Pontieu et al (2007), Zaqarashvili et al (2007), Kim et al (2008), He et al (2009a,b), Okamoto & De Pontieu (2011). In addition, propagating transverse waves in thin threads of solar prominences have been observed (e.g., Lin et al 2007Lin et al , 2009) and Alfvénic waves in bright points have been reported (Jess et al 2009). The role and implications of the observed Alfvénic waves for the heating of the solar atmosphere have been discussed by, e.g., Erdélyi & Fedun (2007); De Pontieu et al (2007); McIntosh et al (2011);Cargill & De Moortel (2011).…”
Section: Introductionmentioning
confidence: 91%
“…Recent observations of Alfvénic transverse waves in spicules have been reported by, e.g, De Pontieu et al (2007), Zaqarashvili et al (2007), Kim et al (2008), He et al (2009a,b), Okamoto & De Pontieu (2011). In addition, propagating transverse waves in thin threads of solar prominences have been observed (e.g., Lin et al 2007Lin et al , 2009) and Alfvénic waves in bright points have been reported (Jess et al 2009). The role and implications of the observed Alfvénic waves for the heating of the solar atmosphere have been discussed by, e.g., Erdélyi & Fedun (2007); De Pontieu et al (2007); McIntosh et al (2011);Cargill & De Moortel (2011).…”
Section: Introductionmentioning
confidence: 91%
“…We have used the averaged values of loop radius and length. However, for kink waves in filament threads (Lin et al 2009) or torsional Alfvén waves in chromospheric magnetic bright points (Jess et al 2009) many have values of k z R ≈ 1. It is relatively straightforward to relax the TT approximation and to consider the effect of the finite tube radius on damping.…”
Section: Spatial Damping Beyond the Tt Approximationmentioning
confidence: 99%
“…To do so, we set the wavenumber component in the perpendicular direction to magnetic field lines to a fixed value, k z L = π/2, with L a typical length-scale in the perpendicular direction. Since highresolution observations of filaments (see, e.g., Lin et al 2007Lin et al , 2009 show fine structures (threads) with a typical width of ∼100 km, we select L = 10 5 m as our perpendicular lengthscale. Therefore, the propagation angle θ now depends on k x , We see that the behavior of the three solutions is substantially different from that of the free propagation case.…”
Section: Constrained Propagation By a Waveguidementioning
confidence: 99%